Nucleation mechanism of intra-granular blisters in tungsten exposed to hydrogen plasma. (October 2020) - Chen, W.Q.; Wang, X.Y.; Li, K.L.; Wang, Y.N.; Morgan, T.W.; Xu, B.; Chiu, Y.L.; Liu, W.
Abstract: Despite being a subject of long-term research on fusion-reactor structural materials, the behaviour of hydrogen in tungsten under plasma exposure remains unclear. Here, the explicit transmission electron microscopy observations for recrystallised W after hydrogen plasma exposure are successfully obtained. These are the first observations to show the intra-granular blisters are located on the {100} planes. Molecular dynamics simulations confirm the hydrogen blister initiating at <100> dislocation core behaved similarly to those in experiment. We propose that the widely reported intra-granular hydrogen blisters are nucleated at the <100> edge dislocation core and develop along the (100) plane in tungsten. Graphical abstract: Image, graphical abstract